2022
DOI: 10.3390/land11071001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Soil Nutrients and Their Ecological Stoichiometry in Different Land Use Types in the Nianchu River Basin

Abstract: Land use types can cause changes in soil chemical characteristics, such as altering soil C, N, and P contents and distribution. The aim of this study was to investigate the status of soil C, N, P and other nutrient contents and their stoichiometric ratios in the terrestrial ecosystem of Nianchu River Basin, Tibet. A total of 102 sample plots with 306 soil samples and 102 plant samples were investigated in August 2021 along the Nianchu River basin by selecting four land-use types: grassland, shrubland, forestla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…While the soil P value in monoculture garden shows the highest value although the difference is not significant compared to other land types. These findings are consistent with the research conducted by Liu et al (2022), which reported higher levels of soil organic matter, soil phosphorus, and soil C/N content in agricultural land compared to other land types. Similarly, Kwiatkowski and Harasim (2020) found that both organic and conventional agricultural land improved the quality of soil chemical properties.…”
Section: Characteristics Of Soil Physical and Chemical Properties In ...supporting
confidence: 92%
“…While the soil P value in monoculture garden shows the highest value although the difference is not significant compared to other land types. These findings are consistent with the research conducted by Liu et al (2022), which reported higher levels of soil organic matter, soil phosphorus, and soil C/N content in agricultural land compared to other land types. Similarly, Kwiatkowski and Harasim (2020) found that both organic and conventional agricultural land improved the quality of soil chemical properties.…”
Section: Characteristics Of Soil Physical and Chemical Properties In ...supporting
confidence: 92%
“…However, most previous studies have examined C:N:P stoichiometry in leaves ( Lanuza et al., 2019 ; Li et al., 2021 ), and relatively little is known about root stoichiometry, especially for fine roots ( Makita et al., 2011 ; Wang et al., 2020 ; Zou et al, 2021 ), presumably because it is more difficult to collect roots than leaves. Moreover, some current studies focused on the C:N:P stoichiometry of soils ( Liu et al., 2022 ; Huang et al., 2023 ) or fine roots ( Geng et al., 2022 ; Hu et al., 2022 ) and less on the nutrient relationships between soils and fine roots ( Zhang et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Tibetan Plateau, the soil microbial-biomass-carbon-to-phosphorus ratio (MBC:MBP) is higher than the global average, which correlates with the relative nutrient limitation of its soils. The C:N and carbon-to-phosphorus (C:P) ratios in soils in the Tibetan plateau are significantly lower than the global average [41,48]. This indicates that soil microbes are relatively more C-limited and are expected to have a higher carbon use efficiency (CUE) [17].…”
Section: Stoichiometry Characteristics Of Soil Microbial Biomass In A...mentioning
confidence: 99%